Sångpraktiker inom den svenska idrottsrörelsen (ca 1872–1939) - Ahlsved, Kaj (Idrott, historia och samhälle, 2025)
Like the temperance, youth and labour movements, the sport movement was a nation-building mass movement. The Swedish sport movement was driven by certain ideals (e.g. patriotism), even if they were not always explicit. Sport leaders rarely discussed their ideological foundations but relied on the ’power of example’, i.e. competition and showcasing, not speeches and writings, were the best way to spread interest in sport. The purpose of this article is to analyse the use of music in the Swedish sport movement from the perspective of sport’s lukewarm interest in an outspoken ideology. By studying songs from three different context within in the Swedish sport movement (gymnastics, association football and the workers sport movement), the study offers a new understanding of music-making in the context of sport and how ideological goals were articulated through musical activities.